2001
DOI: 10.1051/0004-6361:20000015
|View full text |Cite
|
Sign up to set email alerts
|

XMM-Newton EPIC observation of SMC SNR 0102-72.3

Abstract: Abstract.Results from observations of the young oxygen-rich supernova remnant SNR 0102−72.3 in the Small Magellanic Cloud during the calibration phase of the XMM-Newton Observatory are presented. Both EPIC-PN and MOS observations show a ringlike structure with a radius of ∼15 already known from Einstein, ROSAT and Chandra observations. Spectra of the entire SNR as well as parts in the eastern half were analyzed confirming shocked hot plasma in non-uniform ionization stages as the origin of the X-ray emission. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In 10 subregions we found Ne abundances significantly higher than cosmic value, with an average Ne/Ne = 1.7 ± 0.2 over all the subregions. Typically the Ne overabundance is associated with overabundances of O, Mg, Si (Sasaki et al 2001) and Fe and is a clear signature of the ejecta, but this is not the case, since Fe is underabundant and we found solar O abundances. Similar values of the Ne abundance in the Vela SNR were found by Plucinsky et al (2002), who showed that the Vela Bullet D X-ray emission can be described with a non-equilibrium of ionization model (which seems to exclude that Bullet D is a fragment of ejecta) with Ne/Ne ≈ 2.…”
Section: Spectral Analysismentioning
confidence: 62%
“…In 10 subregions we found Ne abundances significantly higher than cosmic value, with an average Ne/Ne = 1.7 ± 0.2 over all the subregions. Typically the Ne overabundance is associated with overabundances of O, Mg, Si (Sasaki et al 2001) and Fe and is a clear signature of the ejecta, but this is not the case, since Fe is underabundant and we found solar O abundances. Similar values of the Ne abundance in the Vela SNR were found by Plucinsky et al (2002), who showed that the Vela Bullet D X-ray emission can be described with a non-equilibrium of ionization model (which seems to exclude that Bullet D is a fragment of ejecta) with Ne/Ne ≈ 2.…”
Section: Spectral Analysismentioning
confidence: 62%
“…They concluded that abundance inhomogeneities exist in the plasma. The insufficiency of a single T e -plasma to parameterize the global spectrum was confirmed by Sasaki et al (2001) with XMM-Newton EPIC PN data; these authors invoked two plasma components and additionally examined distinct regions of the remnant.…”
Section: Caveat On Global Line Ratiosmentioning
confidence: 93%
“…Since the northern portion of the remnant displays a linear shelf appearance, it is conceivable that the expanding ejecta has encountered a dense region of the circumstellar medium (CSM); the higher density would encourage more rapid ionization. Sasaki et al (2001) examined EPIC PN spectra from a northeastern segment (eastward of the shelf ) and from the bright X-ray arc in the southeast. They found that the northern spectrum had a higher fitted temperature and an order of magnitude higher ionization timescale than the southern region, indicating higher ionization.…”
Section: Caveat On Global Line Ratiosmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the brightest SNR in X-rays in the Small Magellanic Cloud (SMC). E0102 has been extensively imaged by Chandra (Gaetz et al 2000;Hughes et al 2000) and XMM-Newton (Sasaki et al 2001). Figures 1 and 2 show images of E0102 with the relevant spectral extraction regions for each of the instruments included in this analysis.…”
Section: The Snr 1e 01022-7219mentioning
confidence: 99%